Development of complete hydrometallurgical processes for gold recovery from ICs and CPUs using ionic liquids - Moisés Gómez; Sue Grimes; Geoff Fowler (Journal of Environmental Management, 2024)

Experimental investigation of products from thermal treatment of real-world mixed single-use and multi-layered waste plastics - Uduak Bassey; Alex Bowles; Geoff Fowler; Abasi-ofon Tom; Gesa Beck; Satyanarayana Narra; Michael Nelles; Michael Hartmann (Environmental Research, 2024)

Novel resource-efficient recovery of high purity indium products: Unlocking value from end-of-life mobile phone liquid crystal display screens - Moisés Gómez; Sue Grimes; Liyao Yang; Tharit Pornsirianant; Geoff Fowler (Journal of Environmental Chemical Engineering, 2023)

Novel closed-loop recovery of light rare earth elements, as their oxides, from end-of-life mobile phone speakers using [Hbet][Tf2N] - Moisés Gómez; Sue Grimes; Danial Bin-Jamaludin; Geoff Fowler (Journal of Environmental Chemical Engineering, 2023)

Novel hydrometallurgical process for the recovery of copper from end-of-life mobile phone printed circuit boards using ionic liquids - Moisés Gómez; Sue Grimes; Geoff Fowler (Journal of Cleaner Production, 2023)

Critical and strategic metals in mobile phones: A detailed characterisation of multigenerational waste mobile phones and the economic drivers for recovery of metal value - Moisés Gómez; Sue Grimes; Yuting Qian; Yexin Feng; Geoff Fowler (Journal of Cleaner Production, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Responding to Climate Change: Participatory Evaluation of Adaptation Options for Key Marine Fisheries in Australia’s South East - Emily Ogier; Sarah Jennings; Anthony Fowler; Stewart Frusher; Caleb Gardner; Paul Hamer; Alistair J. Hobday; Adrian Linanne; Stephan Mayfield; Craig Mundy; Andrew Sullivan; Geoff Tuck; et al. (Frontiers in Marine Science, 2020)